Protein and carbohydrate fractionation of Jiggs Bermudagrass in different seasons and under intermittent grazing by Holstein cows (Acta Scientiarum. Animal Sciences, 2019)
Jiggs bermudagrass has presented competitive production potential over other forages. However, there is a lack of information about the nutritional value of this forage with important relevance in ruminant nutrition. This study aimed to evaluate the protein and carbohydrate fractionation of Jiggs bermudagrass in different seasons of the year under intermittent grazing by Holstein cows. The experiment was conducted during one year in a completely randomized design with nine replications and treatments consisted of the effect of four seasons: fall, winter, spring and summer. The results showed that there were seasonal variations in the fractions of proteins and carbohydrate, with the exception of the protein fraction B3. The better climatic conditions in spring and summer contributed to an increase in the protein fraction A and carbohydrate A+B1. The winter had a greater fraction C of protein and carbohydrate, reflecting the nutritive value of the forage. The use of irrigation during fall and winter had a positive effect on nitrogen fractions B1 and B2 and on non-fiber carbohydrates.